Zakat of free professions between the accounting of zakat and the existing reality. An analytical study of a sample of self-employe - Maustapha Naama; Mohamed Farhi (Dirassat Journal Economic Issue, 2016)
This paper shows the extent of knowledge and awareness of self-employed concerning Zakat , its importance and the conditions as when it is obligatory , as well as how to calculate it , and comparing what came in Accounting Zakat in liberal professions to know whether the owners of these professions calculation method of Zakat is the same way as it is calculated according to the provisions of the legitimacy and accounting principles , which came in Zakat such accounting professions through analytical study of a sample of self-employed Including accountants, doctors engineers and lawyers ,these are supposed to be educated and have a scientific and religious background , and after analyzing the questionnaire by spss program and getting the results ,as a study it can be generalized and applied on self-employed people.